Impact of textile dyeing effluents on germination, growth, yield and nutritional quality of tomato (Solanum lycopersicum L.) (Bangladesh Journal of Agricultural Research, 2026)
An experiment was conducted at the experimental field of the Soil Science Division, Bangladesh Agricultural Research Institute (BARI) during 2017-18 to find out the impact of textile dyeing effluents on germination and seedling stage for the production of Tomato. There were six treatments comprising five concentrations of textile dyeing effluents along with ground water as control treatment for irrigation purposes and tomato (var. BARI tomato-15) was used as plant material. In most of the cases 100% ground water irrigation (T6 treatment) treated plant showed the best result regarding plant characteristics such as germination percentage (100%), fresh weight of fruit (70.00 g), yield/plant (1867g) which were statistically identical to waste water 20% + 80% of pure water treatment (T5). On the other,  waste water 100% + pure water 0% (T1 treatment) showed the lowest result were germination percentage (66.67%), fresh weight of fruit (59.21g) and yield/plant (553 g). T6 treatment showed the highest amount of ascorbic acid (1.34 mg/100 g) and β-carotene (0.08 mg/100 g) and the lowest amount (0.65 mg/100 g and 0.02 mg/100 g, respectively). The accumulation of heavy metals such as Zn, Fe, Cu, Pb accumulated in fruits at the rate of 3.95-9.73, 3.34-9.42, 4.43-11.31 and 2.79-6.19 ppm, respectively. Among these T1, T2, T3 and T4 treated samples, those containing Zn, Fe, Cu and Pb exceed the WHO recommended permissible limit. So, it can be suggested that, selected wastewater of a dyeing factory should be applied as irrigation water for the purpose of crop production as well as tomato cultivation.Bangladesh J. Agril. Res. 48(1): 91-100, March 2023